2007
DOI: 10.1051/0004-6361:20065694
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismology of $\mathsf{\alpha}$ Centauri A

Abstract: Context. Asteroseismology provides a unique tool for studying stellar interiors. Recently p modes have been detected on the bright solar-like star α Cen A thanks to high-precision radial-velocity measurements. However, a better characterisation of these p modes is clearly needed to constrain theoretical models. Aims. We observed α Cen A during five nights using the HARPS spectrograph in order to improve our knowledge of the seismic properties of this star. Methods. We performed high-precision radial-velocity s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 31 publications
4
69
2
Order By: Relevance
“…Therefore, activity noise is not fully included. Sousa et al (2008); (b) Bedding et al (2007); (c) Bazot et al (2007); (d) Bouchy et al (2005); (e) Teixeira et al (2009). ST is for spectral type and T exp for exposure time.…”
Section: Generating Synthetic Rv Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, activity noise is not fully included. Sousa et al (2008); (b) Bedding et al (2007); (c) Bazot et al (2007); (d) Bouchy et al (2005); (e) Teixeira et al (2009). ST is for spectral type and T exp for exposure time.…”
Section: Generating Synthetic Rv Measurementsmentioning
confidence: 99%
“…It has been shown that these anomalies are due to a problem in the guiding engine of the telescope, resulting in poor guiding precision (e.g. Teixeira et al 2009;Bedding et al 2007;Bazot et al 2007;Carrier & Eggenberger 2006). The data for α Cen B, taken in 2009, does not exhibit these peaks because of the corrections made to the guiding software.…”
Section: Velocity Power-spectrum Densitymentioning
confidence: 99%
“…Therefore, for a slowly rotating Sun-like star we may make the approximation that 4) where Ω/2π is equivalent to the rotational splitting which is often denoted by δν. In most studies this is what is used when fitting oscillation spectra in order to measure the mean rotation of stars (Bazot et al 2007, Appourchaux et al 2008, Lund et al 2014a). …”
Section: Measuring Differential Rotation With Asteroseismologymentioning
confidence: 99%
“…However, few binary systems have solar-like oscillations detected in both components. Three systems exist in which the two components have been observed separately: α Cen A (e.g Bouchy & Carrier 2002;Bedding et al 2004;Fletcher et al 2006;Bazot et al 2007), and B (Carrier & Bourban 2003;Kjeldsen et al 2005), 16 Cyg A and B (KIC 12069424 and KIC 12069449;Metcalfe et al 2012Metcalfe et al , 2015Davies et al 2015), and HD 176071 (KIC 9139151 and KIC 9139163;Appourchaux et al 2012). Additionally, oscillations in both components of HD 177412 (HIP 93511) have been measured while observed as a single Kepler target, KIC 7510397 (Appourchaux et al 2015).…”
Section: Introductionmentioning
confidence: 99%